Interdisciplinary social needs response team: A community case study in social needs targeted care during the COVID-19 pandemic and beyond - Mullen, Isabelle; Mariano, Melanie Agnes; Aysola, Jaya (Frontiers in Public Health, 2022)
This case study illustrates the role and value of a social needs response team during times of crisis and beyond. The COVID-19 pandemic resulted in two simultaneous crises—the infectious disease crisis and the socioeconomic crisis. Unemployment and lost wages, housing and food insecurity, and increased childcare needs are just a few examples of the socioeconomic needs that skyrocketed during the COVID-19 pandemic. At the start of the pandemic, the University of Pennsylvania Health System (UPHS) formed an interdisciplinary team of physicians, social workers, nurse practitioners and students of these professions to reimagine social needs screening in a way that could reach people during the pandemic and provide sustainable support for individual's evolving social needs. The Social Needs Response Team (SNRT) at UPHS utilized various secure platforms to keep members of the team connected with each other and their patients. Orientations for participating students included training on how to employ principles of crisis intervention theory, empathetic inquiry, and patient-led and family-centered care to best uncover and serve the needs of their patients. Alongside the illustrative case study, this piece details guiding principles and concepts that are essential to integrating social needs targeted care.